Recurrent miscarriage and pre-eclampsia : the roles played by the immune system and antioxidants - Wilson, Rhoda (World Scientific, 2004)
This book examines the role of antioxidants and of the immune systemin the pathogenesis of pre-eclampsia and recurrent miscarriage. Whilstmany papers have discussed the role of antioxidants in pre-eclampsiaand, that of the immune system, hitherto publication has notconsidered the two simultaneously.